Critical Reception and Postmodern Violation of Generic Conventions in Jacques Brossard’s "Monument aux marges": L’Oiseau de feu - Ransom, Amy J. (Studies in Canadian Literature, 2008)
Québec writer Jacques-Edmond Brossard’s 1989 novel, L’oiseau de feu-1. Les années d’apprentissage, first of the five-part Oiseau series, created a literary sensation as a potential monument of la science-fiction québécoise. Despite critical approbation, however, few readers endeavour beyond the series’ first instalment, and the whole stands at the margins of the field both for readers and scholars. In part, the difficulty of identifying Brossard as primarily a mainstream or a science-fiction writer has estranged fans and critics of both camps. But more importantly, his series’ ludic irreverence toward and self-conscious play with generic conventions – one of its many postmodern features – works against its long-term engagement of québécois/French-Canadian critics in both the mainstream and the genre milieux. Yet, this "monument aux marges" deserves more attention precisely because of its postmodernism.